2016
DOI: 10.1590/s0100-204x2016000500015
|View full text |Cite
|
Sign up to set email alerts
|

Identification and field evaluation of the sex pheromone of a Brazilian population of Spodoptera cosmioides

Abstract: -The objective of this work was to identify the sex pheromone of Spodoptera cosmioides and to evaluate whether there is pheromone cross-attraction in Spodoptera sp. (Lepidoptera: Noctuidae). Spodoptera cosmioides gland extracts were analyzed by GC-FID and GC-MS. Wind tunnel and electrophysiology experiments were conducted to evaluate the role of gland compounds. In the field, different pheromone traps were tested: S. frugiperda commercial lure; (9Z)-9-tetradecenyl acetate (Z9-14:OAc) and (9Z,12E)-9,12-tetradec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Other studies have focused on the interactions of S. cosmioides with intrinsic defenses of the plants themselves, chemical insecticides and Bt proteins (BERGAMASCO et al, 2013;BERNARDI et al, 2014;BOIÇA Jr. et al 2015;SILVA et al, 2016;MACHADO et al, 2020;QUEIROZ et al, 2020). In addition, several studies have been devoted to studying semiochemicals (BLASSIOLI-MORAES et al, 2016) and interactions with natural enemies, especially parasitoids of eggs, larvae and pupae (GOULART et al, 2011a;2011b;ZACHÉ et al 2012;CABEZAS et al 2013a;FREITAS et al, 2018;.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have focused on the interactions of S. cosmioides with intrinsic defenses of the plants themselves, chemical insecticides and Bt proteins (BERGAMASCO et al, 2013;BERNARDI et al, 2014;BOIÇA Jr. et al 2015;SILVA et al, 2016;MACHADO et al, 2020;QUEIROZ et al, 2020). In addition, several studies have been devoted to studying semiochemicals (BLASSIOLI-MORAES et al, 2016) and interactions with natural enemies, especially parasitoids of eggs, larvae and pupae (GOULART et al, 2011a;2011b;ZACHÉ et al 2012;CABEZAS et al 2013a;FREITAS et al, 2018;.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, Z 11‐16:OAC was released at 0.06 ng mg −1 , 2× less than Z 9‐14:OAC. This compound is also produced in several other species of moths, always as a minor component in the pheromonal mixture, e.g., in Spodoptera cosmioides (Walker) (Blassioli‐Moraes et al, 2016), Spodoptera eridania (Cramer) (Teal et al, 1985), Spodoptera desconsi Lalanne‐Cassou & Silvain (Monti et al, 1997), Sp odoptera praefica (Grote) (Landolt et al, 2003), Sp odoptera sunia (Guen) (Bestmann et al, 1988), and Spodoptera exigua (Hübner) (Mitchell & Tumlinson, 1994). Our study found that the response of T. pretiosum to this pheromone is dose dependent and that the proportion between the compounds may help them distinguish different hosts in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, these stimuli can be detected by gas chromatography coupled to electroantennographic detection (GC-EAD). This technique has greatly aided the discovery of compounds with an attractive (Rojas et al 2006;Milet-Pinheiro et al 2013Blassioli-Moraes et al 2016;Yan et al 2018) and insect-repellent actions (Yang et al 2009;Zhang et al 2013;Uniyal et al 2014), be they major or minor compounds (Mccormick et al 2014). Substances with attractive action, such as pheromones, have been used in pest monitoring and controlling for mass collection and mating disruption (Zarbin & Rodrigues 2009;Cui & Zhu 2016;El-Shafie & Faleiro 2017).…”
Section: Introductionmentioning
confidence: 99%
“…2013, 2015; Blassioli‐Moraes et al . 2016; Yan et al . 2018) and insect‐repellent actions (Yang et al .…”
Section: Introductionmentioning
confidence: 99%